2021
DOI: 10.4049/jimmunol.2000797
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitogenic and Regulatory CD8 T Cells in Multiple Sclerosis and Its Animal Models

Abstract: Multiple sclerosis (MS), a neuroinflammatory disease that affects millions worldwide, is widely thought to be autoimmune in etiology. Historically, research into MS pathogenesis has focused on autoreactive CD4 T cells because of their critical role in the animal model, experimental autoimmune encephalomyelitis, and the association between MS susceptibility and single-nucleotide polymorphisms in the MHC class II region. However, recent studies have revealed prominent clonal expansions of CD8 T cells within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Interestingly, some of the transcripts upregulated in cluster 1 microglia from middle-aged mice are involved in the assembly and function of proteasomes and processing of MHC Class I restricted peptides. Although our model of EAE is CD4 + T cell-driven, CD8 + T cells are more prevalent than CD4 + T cells in human MS lesions, including in the chronic active lesions that are typical of pMS (3032). The emergence of microglia particularly well-equipped to activate CD8 + T cells might be relevant to the pathogenesis of pMS.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, some of the transcripts upregulated in cluster 1 microglia from middle-aged mice are involved in the assembly and function of proteasomes and processing of MHC Class I restricted peptides. Although our model of EAE is CD4 + T cell-driven, CD8 + T cells are more prevalent than CD4 + T cells in human MS lesions, including in the chronic active lesions that are typical of pMS (3032). The emergence of microglia particularly well-equipped to activate CD8 + T cells might be relevant to the pathogenesis of pMS.…”
Section: Discussionmentioning
confidence: 97%
“…Although CD4 + T cells, both CD4 + Teff and CD4 + FoxP3 + Treg cells, are the traditional primary actors in MS/EAE disease pathogenesis and immunoregulation, emerging evidence shows that CD8 + T cells also have roles in both immunopathology and immunoregulation, either to exacerbate or mitigate brain inflammation during CNS autoimmunity 78,79 . Regarding the MS/EAE immunopathogenesis aspect, myelin-specific CD8 + T cells exacerbate brain, though not spinal cord, inflammation via a Fas liganddependent mechanism to promote lesion formation in the brain 80 . In addition, IL-17A secreting CD8 + T cells, termed Tc17 cells, in the CNS support Th17 cell-mediated autoimmune encephalomyelitis 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammatory Th cell subsets have long been regarded as the main effectors of MS pathogenesis, an important pathophysiological role of CD8 + T cells has also recently been recognized. Histopathological studies of immune cell infiltrates in post-mortem brain tissues from MS patients showed a prevalence of CD8 + T cells compared to CD4 + T cells ( 105 , 145 ). Moreover, sRNA-seq analyses revealed a prominent oligoclonal expansion of CD8 + T cells in the peripheral blood and CSF of MS patients ( 146 , 147 ).…”
Section: Dysregulation Of Astrocyte Functions By Inflammatory T Cells...mentioning
confidence: 97%
“…The immunopathogenesis of MS relies on the recruitment of specific autoreactive Th cell subsets and CD8 + T cells within CNS where they are reactivated and secrete cytokines and chemokines that modulate the activity of several glial cells, including astrocytes ( 11 , 105 ). Among Th cells, Th1, Th17 and Th1-like Th17 cells have been identified as key players of MS pathogenesis, by producing one or more lineage-defining cytokines, which affect several astrocyte functions as discussed below ( Figure 1 ).…”
Section: Dysregulation Of Astrocyte Functions By Inflammatory T Cells...mentioning
confidence: 99%